PENGARUH RETURN ON INVESTMENT (ROI) DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM SYARIAH (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Pada Indeks Saham Syariah Indonesia Periode 2012-2016) - Dian Maulita; Muhammad Arifin (Jurnal Manajemen, 2018)
This study was conducted to analyze the influence of Return On Investment (ROI) and Earning Per Share (EPS) on Return of Sharia Stocks in Cases in Manufacturing Companies of Food and Beverage Sub Sector Listed on Indonesia Sharia Stock Index Period 2012-2016. The research method used is an associative quantitative method. This research uses multiple linear regression analysis technique with SPSS VS 20.00. The Sampling technique used is Purposive Sampling and the number of samples used as many as 9 companies. The results of this study indicate that the partial or simultaneous ROI and EPS have no significant effect on stock return sharia.Key word : Stock Return, Return On Investment and Earning Per Share